Isolation and characterization of novel Streptomyces strain from Algeria and its in-vitro antimicrobial properties against microbial pathogens - Fatima Zohra Djebbah; Larbi Belyagoubi; Djamel Eddine Abdelouahid; Farid Kherbouche; Naif Abdullah Al-Dhabi; Mariadhas Valan Arasu; Balasubramani Ravindran (Elsevier, 2021)
Background: The constant development of microbial resistance to the traditional antimicrobial agents and the emergence of new infectious diseases justify the urgent need for new effective antimicrobial molecules. However, the irrational use of antibiotics increases microbial resistance dramatically and along with that the frequency of mortality associated with infections is higher. Therefore, to combat the antimicrobial resistance, the screening of compounds with novel chemical structures is essential. This study intended to determine the antimicrobial potential of Streptomyces GLD22 strain isolated from Algeria. Methods: The characterization of Streptomyces strain GLD22 was performed by physiological, biochemical and molecular tests. The antimicrobial activity was tested by the well diffusion method and the minimum inhibitory concentration value calculation were performed using broth micro dilution technique. The extracellular metabolites profiling was done using GC-MS. Results: Physiological, biochemical and phylogenetic analysis confirmed that the strain GLD22 showed maximum identity towards Streptomyces species. The extra cellular metabolites revealed their antimicrobial activity at 1 mg/ml for Klebsiella pneumoniae, Pseudomonas aeruginosa and Escherichia coli, whereas Staphylococcus aureus, Bacillus cereus and Bacillus subtilis documented 0.5, 1 and 1 mg/ml respectively. GC-MS analysis confirmed that 2-tert-butyl-4,6-bis(3,5-di-tert-butyl-4-hydroxybenzyl) phenol, Dibutyl phthalate and Cyclo(leucyloprolyl) were the major drug molecules present in the extract. Conclusion: The novel Streptomyces strain GLD22 recovered from the Gueldaman cave of Algeria showed better antimicrobial activity towards both Gram positive and Gram negative pathogens. Interestingly, the MIC values were comparable with the standard drug molecules. In addition, the identification of active metabolites present in the crude extracts was an advantage.